2022
DOI: 10.9734/jamps/2022/v24i10579
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Cells Parameters and Complete Blood Count in Diabetic Patients: A Cross-sectional Study

Abstract: Background and Aim: Diabetes is a type of metabolic disorder characterized by increased blood glucose, which is due to insulin resistance, insulin deficiency, or both. Changes in blood cell parameters in diabetes are controversial. The present study aimed to assess the blood cell parameters in diabetic patients compared to healthy individuals. Methods: This cross-sectional study was performed on 540 cases (270 diabetic patients and 270 healthy individuals) over 20 years old who were referred to the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Furthermore, Naredi et al reported that high WBC values may indicate subclinical inflammation in diabetic patients [55]. Besides this study, numerous other studies have reported that WBC counts are significantly higher in diabetic patients than in healthy individuals [54,[56][57][58].…”
Section: Fructosamine and Blood Countsupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, Naredi et al reported that high WBC values may indicate subclinical inflammation in diabetic patients [55]. Besides this study, numerous other studies have reported that WBC counts are significantly higher in diabetic patients than in healthy individuals [54,[56][57][58].…”
Section: Fructosamine and Blood Countsupporting
confidence: 55%
“…The WBC count in the blood count test can demonstrate the presence of inflammation in many diseases [53]. Therefore, increased WBC levels may predict a further decline in insulin activity and the progression of diabetes [54]. Furthermore, Naredi et al reported that high WBC values may indicate subclinical inflammation in diabetic patients [55].…”
Section: Fructosamine and Blood Countmentioning
confidence: 99%